Modernising Local Government by Fragmentation: Lessons From The Portmore Municipal Experiment - Jamaica (Commonwealth Journal of Local Governance, 2010)
Modernization of local government leads inevitably to the vexed question of how to structure local government to meet the changed circumstances in which it operates. This acknowledgement is no less so for the Caribbean in general and Jamaica in particular, where forces such as increased suburbanization and higher level of citizen demands on local government have prompted policy to respond to the changing world of local government. The recalibration of local government structure serves key objectives – to achieve economies of scale; to assure organisational viability and to reinvigorate local democracy. The Portmore Municipal Council (PMC) in Jamaica, enacted by the Municipalities Act of 2003 is representative of fragmentation of local government and innovates local policy and administration in two ways: (a) popular election of Mayor; and (b) construction of local/community self-management institutional arrangements. This paper reviews the experience of the PMC during its formative years of operation to determine the extent to which the philosophy and practice of local/community self-management norms are being institutionalised into the operations of the municipality and identify lessons for the broader adoption of a process of municipalisation.